Menjembatani Aturan dan Kebutuhan: Kajian Kebijakan atas Pendirian Rumah Ibadah Tanpa Izin di Papua Barat - Miftahul Mungin (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article examines the issue of the construction of houses of worship without permits in West Papua Province, which is rooted in a mismatch between government regulations and the real needs of the community. The main problem stems from the inconsistent implementation of Joint Ministerial Regulations (PBM) Numbers 9 and 8 of 2006, which contain articles subject to multiple interpretations and influenced by local political pressure. This situation is exacerbated by unclear oversight and law enforcement mechanisms, as well as the structural weaknesses of the Interfaith Harmony Forum (FKUB), which is often not neutral. As a result, many houses of worship are built without formal permits, triggering social conflict and resulting in demolitions that create trauma within the community (Azra, 2018; Lubis, 2019). To address this problem, three policy alternatives are analyzed: revitalizing the PBM, establishing an independent monitoring team, and reforming the FKUB. This article uses qualitative methods with descriptive and ultrasound analysis approaches, as well as William N. Dunn's theory. The establishment of an independent monitoring team is considered the most effective and responsive alternative (score 22). This team will have the authority to monitor, mediate, and recommend sanctions, thus bridging the gap between regulations and community needs fairly (Prasetyo, 2021). Therefore, the proposed policy recommendation is the establishment of an independent monitoring team under the Regional Office of the Ministry of Religious Affairs of West Papua Province as a strategic solution to ensure a transparent and accountable licensing process, for the sake of sustainable harmony.